2017
DOI: 10.1016/j.tranpol.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Improving paratransit service: Lessons from inter-city matatu cooperatives in Kenya

Abstract: While providing essential access for large portions of city populations, the quality of paratransit services in Sub-Saharan African cities is poor. Poor quality of service can be attributed to two features of the paratransit business operating model: driver remuneration on the basis of a daily 'target system'; and cash-based business management in which vehicle depreciation is ignored as an operating expense. In Kenya, the voluntary organisation of fragmented inter-city matatu businesses into Savings and Credi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…From Lagos to Johannesburg to Nairobi, paratransit is common. One of the practices that transport scholars consider to be most responsible for the poor service of paratransit is what is referred to as the 'target system', whereby operators pay owners of vehicles a target amount at the end of every day (Behrens et al 2017). Although Mutongi and others have shown that passengers often pressure drivers into bad driving behaviour, it is argued that target systems 'create strong structural incentives for drivers to compete aggressively for passengers in the road space, overload vehicles, speed as they attempt to increase the number of service trips during peak periods, and delay departures from termini until the vehicle is full during off-peak periods' (ibid.…”
Section: Moving Targetsmentioning
confidence: 99%
“…From Lagos to Johannesburg to Nairobi, paratransit is common. One of the practices that transport scholars consider to be most responsible for the poor service of paratransit is what is referred to as the 'target system', whereby operators pay owners of vehicles a target amount at the end of every day (Behrens et al 2017). Although Mutongi and others have shown that passengers often pressure drivers into bad driving behaviour, it is argued that target systems 'create strong structural incentives for drivers to compete aggressively for passengers in the road space, overload vehicles, speed as they attempt to increase the number of service trips during peak periods, and delay departures from termini until the vehicle is full during off-peak periods' (ibid.…”
Section: Moving Targetsmentioning
confidence: 99%
“…The vast majority of research on transportation in developing countries has a strong focus on policy. Examples include explorations on how capacity-building of operators could inform the public transport reform process [75]; the progress, process, and risks of engaging operators for public transport reform in Cape Town, South Africa [76]; policy challenges in developing countries on hybrid urban transport systems caused by the complexities and constraints of old, existing systems [25]; the organization and improved services of inner-city Matatu (taxis) and the potential for their transferability [8]; and the structuring of a user satisfaction model based on observed and unobserved variables from commuters in Nairobi, Kenya [30]. We also encountered literature on the role played by motorcycle taxis in providing IPT: they contribute to increased employment opportunities [62], improve access and last mile distribution [32], increase women ridership in urban areas [71], and potentially expand urban transportation systems [21].…”
Section: Transportation In Urban African Citiesmentioning
confidence: 99%
“…In every city, paratransit services provide crucial means of mobility and connectivity for people. Few recent studies investigated the importance of quality and efficiency improvement in providing paratransit services [13,14]. Plano et al [15] performed a survey on driver attitude of interventions in evening paratransit service.…”
Section: Sustainable Transportation and Paratransit Servicementioning
confidence: 99%
“…The heuristics were widely studied for solving ConVRP [25][26][27][28]. Further, the ConVRP problem dealing with different types of customers was solved using a template-based tabu search algorithm proposed by Tarantilis, Stavropoulou, and Repoussis [13]. The algorithm involves a two-level decomposition scheme.…”
Section: Transportation Services With Consistent Schedulementioning
confidence: 99%